2009
DOI: 10.1007/s00415-009-5285-1
|View full text |Cite
|
Sign up to set email alerts
|

Irritability, psychomotor agitation and progressive insomnia induced by bilateral stimulation of the area surrounding the dorsal subthalamic nucleus (zona incerta) in Parkinson’s disease patients

Abstract: Fig. 2 Case 2: a MRI scans from both patients. b Schaltembradt atlas images have been superimposed to show DBS electrodes location. c UPDRS irritability and anxiety score changes with different stimulation parameters. d Sleep duration changes with different stimulation parameters

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…The effects of STN and ZI DBS have been poorly documented to date. One report has shown that ZI DBS could improve anxiety and depression in PD patients (Burrows et al, 2012), while another has reported that either STN or ZI DBS could lead to psychiatric complications like irritability, psychomotor agitation and severe progressive insomnia (Merello et al, 2009). Our results suggest that this area should be taken into accounts carefully.…”
Section: Discussionmentioning
confidence: 99%
“…The effects of STN and ZI DBS have been poorly documented to date. One report has shown that ZI DBS could improve anxiety and depression in PD patients (Burrows et al, 2012), while another has reported that either STN or ZI DBS could lead to psychiatric complications like irritability, psychomotor agitation and severe progressive insomnia (Merello et al, 2009). Our results suggest that this area should be taken into accounts carefully.…”
Section: Discussionmentioning
confidence: 99%
“…The importance of lead position was highlighted by Mercello and colleagues [25]. They presented two cases in which the area surrounding the dorsal STN (including the zona incerta) was stimulated as well as the STN itself.…”
Section: Deep Brain Stimulationmentioning
confidence: 97%
“…Moreover, stimulation of the rostral ZI induced side effects in some patients, i.e. speech deterioration and a sense of disequilibrium during walking [47], as well as irritability, psychomotor agitation and severe progressive insomnia [48]. The former disturbances were not present after stimulation of the caudal ZI [47].…”
Section: Active Target For Dbs Outside the Stn: The Zimentioning
confidence: 99%